The Code Decoded. A user's guide to the International Code of Nomenclature for algae, fungi, and plants - Nicholas Turland (Pensoft Publishers, 2019)
The purpose of this second edition of The Code Decoded is to serve as a user's guide to the International Code of Nomenclature for algae, fungi, and plants ("Code"), specifically the Shenzhen Code (Turland & al., 2018).